Mapping gamma radiation and its uncertainty from weathering products in a Tasmanian landscape with a proximal sensor and random forest kriging - Viscarra Rossel, Raphael; Webster, R.; Kidd, D. (2014)
The radionuclides of potassium (40K), uranium (238U) and thorium (232Th) emit from the land surface gamma radiation that is characteristic of the underlying rocks and the distribution of their weathering products in the landscape. We measured the radiation along widely separated transects using a mobile proximal sensor over a 10 000-ha region of Tasmania. We supplemented the transect data with information from soil and geological maps and dense data from LandSat and SPOT imagery, a digital elevation model and terrain attributes on a grid at 30-m intervals so as to map the radionuclides. We used a sequence of steps, starting with a spatial bootstrap and random forests to predict emissions across the study area and at sampling points excluded from the bootstrap samples. The predictions at the sampling points were compared with the observed values to obtain residuals, which were then used to krige them at all points on the 30m grid. We combined the random forest and kriging predictions on the 30-m grid to obtain our random forest kriging predictions. Repeating the procedure 100 times provided confidence limits on our results and predictions. The resulting maps of the radionuclides accord well with what we know of the soil, lithology and topography of the region from other sources. Alluvial deposits with large amounts of potassium extend from the foot slopes of the Great Western Tiers and along the flood plains of the Meander River, providing evidence of previous widespread weathering and deposition of the material. The fertile Red Ferrosols (roughly equivalent to Ferralic Nitisols in the World reference base (WRB) classification) on the extensive Tertiary basalt plateau emit little gamma radiation as a result of deep weathering and of potassium movement and accumulation down its talus slopes. The maps show the complexity of the region in terms of soil, lithology and terrain, and they show the merits of gamma radiometry for mapping and understanding the distribution of materials in such regions. © 2013 John Wiley & Sons, Ltd.